Edukasi dan Sosialisasi Pencegahan Virus Covid-19 Berawal Dari Diri Sendiri Di Desa Kampung Anyar Kecamatan Glagah Kabupaten Banyuwangi - Feby Indriana Yusuf; Dzurotul Mutimmah; Novi Prayekti; Reny Eka Evi Susanti; Fitri Nurmasari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The Corona virus is one of the viruses that has caused SARS, MERS, and Covid-19. Banyuwangi Regency is one of the areas with a graph of the development of Covid-19 which shows a fairly high increase. Based on data from the corona.banyuwangikab.go.id website in August, 237 people were declared infected with Covid-19, in December there were 3963 people. This is the main concern of many parties, especially local governments, in an effort to prevent the spread of the Covid-19 virus. Glagah sub-district is one of the sub-districts located in the western part of the Banyuwangi region. Kampung Anyar Village is one of the villages in Glagah District. Many people in Kampung Anyar village still do not comply with health protocols, so that good activities in the form of socialization through banners, through social networks and through other community activities are needed to be able to successfully break the chain of the Covid-19 virus. In addition to socialization related to health protocols, education to residents must be provided so that in implementing health protocols it can be carried out according to rules and recommendations, so that the community, through the smallest scope, namely families, can protect and protect each other from being infected with the Covid-19 virus. This activity raises the awareness of the village community in Kampung Anyar that early prevention is not as complicated as heard through social media or television, besides that women who participate in these activities agree and are committed to being the front guard in their families in preventing the spread of Covid-19.